Detection of psychosocial distress in cancer patients: A survey of Mexican oncologists. Issue 6 (2nd November 2022) - Galindo Vázquez, Oscar; Rivera, Samuel; Lerma, Abel; Calderillo Ruiz, Germán; Espinoza Bello, Marcos; Meneses, Abelardo; Lerma, Claudia
Abstract: Purpose: Identification of patients' distress is relevant for an on-time referral to psychosocial treatment. The objective was to assess the implementation of the guidelines for distress managing in Mexican oncologists based on the NCCN guidelines. Design: The study was non-experimental and cross-sectional. Sample: Two hundred thirty-one oncologists participated with an average age of 38 ± 11 years. Methods: The likelihood of distress assessment was quantitatively evaluated. Findings: A high percentage of oncologists knew and used procedures to assess psychosocial discomfort. However, a smaller percentage used a valid and reliable instrument. Factors associated with performing distress identification procedures were knowing the distress guidelines and lack of time. Factors for questionnaire usage are the availability of brief instruments and the percentage of patients suffering from stress. Implications for Psychosocial Providers: Psychosocial providers should develop strategies to educate and ensure that oncologists are familiar with guidelines on distress in oncology. More dissemination of screening procedures and referral to psychosocial programs in oncology is required. Integrating a distress screening program involving psychosocial providers and oncologists should be approached as a routine in high-quality cancer care, to reduce the stigma associated with mental health services.